Cybernetics Approaches in Intelligent Systems Computational Methods in Systems and Software 2017, vol. 1 (Advances in Intelligent Systems and Computing, 2018)
This book discusses new approaches and methods in the cybernetics, algorithms and software engineering in the scope of the intelligent systems. It brings new approaches and methods to real-world problems and exploratory research that describes novel approaches in the cybernetics, algorithms and software engineering in the scope of the intelligent systems. This book constitutes the refereed proceedings of the Computational Methods in Systems and Software 2017, a conference that provided an international forum for the discussion of the latest high-quality research results in all areas related to computational methods, statistics, cybernetics and software engineering.